Analysis of consumer decisions in purchasing potted decorative flowers in Batu City - Imam, Muhammad; Mamilianti, Wenny; Komarudin, Nurul Aini (University of Islam Malang, 2024)
This study aims to identify consumer characteristics and examine the key factors influencing purchasing decisions for potted ornamental flowers in Bumiaji District, Batu City, Indonesia. As a region known for its floral tourism, Batu City offers a growing market for ornamental plants, especially with rising consumer income levels. While previous research has largely focused on personal, cultural, and psychological factors, less attention has been paid to the role of social marketing and shifting consumer preferences in fostering long-term purchase loyalty. Adopting a quantitative approach, this study surveyed 100 respondents and employed logit regression analysis to identify the most influential factors affecting buying behavior. The results indicate that personal, cultural, and psychological factors significantly shape consumer decisions, whereas social factors have no notable impact. This is likely because buying ornamental flowers is largely driven by individual preferences and needs rather than social influence. Variables under the social factor, such as buying based on friends’ suggestions, the perceived social role of the flowers, or general interest due to quality, may not directly relate to peer pressure or social conformity, but instead overlap with personal or psychological motivations. Consumers may prioritize aesthetic appeal, emotional satisfaction, or functional use over social recommendations, which diminishes the relative importance of external social cues in the decision-making process. This suggests that in the context of ornamental plant purchases, decision-making is more introspective and self-directed, highlighting the need for marketing strategies that focus on personal experience, quality, and emotional connection rather than social trends or peer influence.